Penerapan Administrasi Perkara Elektronik (E-Court) dan Pemeriksaan Perkara Secara Elektronik Berdasarkan PERMA No 1 tahun 2019: Studi di Pengadilan Negeri Surakarta Kelas IA Khusus - Diajeng Herda; Sindi Ayu Widiawati; Windiarto Rengga Tony Adendra; Elma Aulia Khoirunisa; Devon Hugo Putra; FX. Hastowo Broto Laksio (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the implementation of electronic court administration (e-court) and electronic case hearings within the judicial system based on Supreme Court Regulation (PERMA) No. 1 of 2019, with a particular focus on the e-filing, e-payment, e-summons, and e-litigation systems. The study applies a juridical-empirical method with a descriptive approach by analyzing relevant legal provisions and observing their practical implementation in the field. The findings indicate that the implementation of e-court has simplified administrative procedures while enhancing efficiency, transparency, and accessibility for justice seekers. Nevertheless, several obstacles persist, including limited user understanding, technical disruptions, and uneven readiness of supporting infrastructure and facilities. Therefore, further improvements are still required to optimize system utilization for all parties involved in legal proceedings. In conclusion, the implementation of electronic case administration under PERMA No. 1 of 2019 has been relatively well executed, although it still necessitates enhancements in public outreach, system reliability, and infrastructural support to fully realize the objectives of a simple, fast, and cost-effective judiciary system.